The analysis of factors that influence stock price volatility on pharmaceutical sub sectors listed on BEI (2010-2020 period) - Azizah Salsabila; Megawati Megawati (Universitas Negeri Padang, 2022)
Stock price volatility is an important factor that investors should look into doing investment activities, because the stock price volatiliy shows the company's risk. Stock prices volatility that are too high, that mean the company’s risk is also high. However, if stock price volatility is too low, often mean that the company's ability to make a profit is poor. There are many factors that can affect stock prices volatility, including Dividend Policy, Leverage, Trading Volume and Asset Growth. The sampling technique is purposeful. The data for this study consisted of listed pharmaceutical sub sectors during 11 years of observation and obtained a sample of 4 companies or 44 sample data. The analysis technique used is multiple linear regression and the test is performed with SPSS version 16. The result shows that Dividend Policy has a significant negative effect on the stock price volatility. While leverage (DPR), Trading Volume, and Asset Growth have no effect on stock price volatility.